Financing the public health system: Defining reference point for optimizing managerial decisions - Stoina Cristian Nicolae (Budgetary Research Review (BRR), 2011)
Financing the public health system represents a central reference point of the decisional algorithm necessary for ensuring an advanced management, in the sense that the purpose of this tactic is to analyse the current financial management, to formulate some observations and to present some authorised recommendations from the experts in the health domain, who could introduce a redesign of the managerial decisions in sanitary units organization, characterised by an institutional culture which is refractory to the changes imposed by hospital services rationalization. The methodological approach of this paper, far from being exhaustive, is based on the analysis of the medical system, with emphasis on financing the medical care services. The evaluation is done by using some technical research instruments, as well as by processing some data with public character available on the official sites of Romanian public institutions, data that provide reliable information, valid for the analysed reference system.
Keywords: H75; I38; 330; health assurance budget; health economics